INTEGRATION OF SPIRITUAL COMMUNICATION, ISLAMIC COMMUNICATION, AND ENVIRONMENTAL COMMUNICATION: [Case Studies On Waste Management, Banten Indonesia] - Armawati Arbi (Universitas Islam Negeri (UIN) Mataram, 2014)
Spiritual communication, Islamic communication, and environmental communication are not yet integrated in Muslim daily life in Tangerang Selatan. The people are not yet aware of maintaining fresh air, clean water, and arable land. Most of them has not applied 2008 law in waste management yet. This research aims to reveal cognitive aspect, attitude, and action/ behavior in daily life. This research uses qualitative approach. The methods of data collection are deep interviews, categories of community, participant observation, conversation, and open question. It has found that frst, most of them, forget that human being as His settlement on earth in Quran. Second, most of them, forget that Allah do give the earth life or dead in Quran. Third, most of them, remember kebersihan sebagian dari iman or hygiene is part of faith as said in Hadith, and most of them, do not know law of 2008 on waste management. Some of them knew how to manage waste on television, as in Daai TV, MetroTV, and JakTV in Indonesia. They supposed servant or parents as dust man at home. Father/mother or servant usually burns organic waste in the empty yard. Their behaviors of RT 03/RW 01 Bambu Apus are included in 5 families in blue one, 5 families in green one, 30 families ,and 4 rental homes in yellow one, and 26 families and 2 rental homes in red ones in four categories of waste management.